Case Study On Hewlett Packard (HP) : Service Oriented Architecture (SOA) To Achieve Business Competitiveness And Globalization - Ng, Mei Chin (2005)
The globalization of computer industries and markets lead to rapid and significant technological change thus contributes to competitive landscape.